(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
Three New compounds N,N(substituted) amino,N(3(2-fluorenyl))propanone-3.(Ia),(Ib),(Ic), have been prepared using Mannich reaction from 2- Acetyl fluorine with formaldehyde and secondary amine. For(diethanol amine, diethyl Amine, N- methyl. N- phenyl amine) in an acidic medium HCl which gave these compounds: )N, N bis (2- hydroxy ethyl) amino, N (3 (2-fluorenyl)) propanone-3 (Ia). )N, N bis (ethyl) amino, N (3 (2- fluorenyl)) prpanone-3 (Ib). N-methyl. N-phenyl amino, N (3 (2- fluorenyl)) propanone-3 (Ic). The structure of these compounds have been checked by spectrum analysis: (IR, 1H-NMR,13c-NMR, LC-MS). تم تصنيع بعض المركبات الجديدةN,Nبيس (مستبدل) أمينو، N (3 (2 - فلورينيل)) بروبانون – 3 (Ic,Ib,Ia) . عبر تفاعل مانيش بدءاً من 2- استيل فلورين مع الفورم ألدهيد وأمين ثانوي، مثال: (دي ايتانول أمين، دي ايتيل أمين، N– ميتيل.N– فينيل أمين)بوجود HCl. وهذه المركبات الجديدة هي: Ia-N,Nبيس(2-هيدروكسي ايتيل) أمينو3)N(2- فلورينيل) بروبانون –3 Ib-N,Nبيس(ايتيل) أمينو، N (3(2- فلورينيل) بروبانون – 3 Ic-(N-ميتيل. - Nفينيل) أمينو،N (3(2 - فلورينيل) بروبانون – 3 تم تحديد بنية المركبات والتعرف عليها باستخدام تحليل أطياف IR و1H-NMR و13C-NMRوLC-MS.